2020
DOI: 10.15640/jeds.v8n2a1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic of Banking Sector in Benin: Do More Competition Imply More Efficiency?

Abstract: This paper examines the dynamics of the financial system including banks and Decentralized Financial Systems (DFS) in Benin. While the reforms have produced the expected effect in terms of financial depth, compared to other developing countries, financial deepening is still weak-despite a remarkable contribution of DFS-with respect to the economy's mediumand long-term production or growth objectives. The result is an expansion of financial dualism with the financial micro intermediationdevelopment. Is the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The first states that increased competition in the banking industry will prompt banks to provide firms with more credit at lower interest rates. By establishing a spatial competition model for loans, Babatoundé (2020) demonstrated that competition can lead to a decline in loan interest rates and a rise in deposit interest rates. Bustos et al (2020) found that bank monopolies are more likely to lead to credit rationing and lower capital accumulation rates than competitive markets.…”
mentioning
confidence: 99%
“…The first states that increased competition in the banking industry will prompt banks to provide firms with more credit at lower interest rates. By establishing a spatial competition model for loans, Babatoundé (2020) demonstrated that competition can lead to a decline in loan interest rates and a rise in deposit interest rates. Bustos et al (2020) found that bank monopolies are more likely to lead to credit rationing and lower capital accumulation rates than competitive markets.…”
mentioning
confidence: 99%